Simulación y optimización por computadora de una planta para la obtención de amoníaco a partir de gas natural - Genovez Alfaro, Nadia Sofía (2006)
Simulation and optimization was carried out using the CHEMCAD 5.2.0 program of an Ammonia Plant using Natural Gas as raw material. The objective of this project is to carry out the calculation and sizing of a plant for the production of 334,000 tons / year of ammonia, from natural gas as raw materials. Considering an average of 1000 tn / day (334 days) of operation of the plant, 41.6 tn / h of NH3 would be obtained, using the CHEMCAD program to determine the optimal variables in each stage. The ammonia produced will be used as raw material to produce fertilizers and other products. Five stages of the process were determined: Reform, Conversion, Purification, Metanation and Ammonia Loop. For each stage the optimum temperature and pressure of operation was determined using the program, as well as the balance of matter and energy in addition to the operation design of each equipment. In addition, the lay out of the plant was carried out, which is the placement of equipment in the field and the economic evaluation of the project. All the more detailed explanation is found in the annexes of the project. The market study shows that the demand for ammonia in Peru is adequate to this amount, but the viability of this project, from the economic point of view, involves the export of a large part of the production of NH3 to the MERCOSUR countries. The production cost of the plant is $ 156.45 / tn ammonia. This value it is below the price used for the sale which is $ 260 / tn ammonia. Using the CHEMCAD 5.2.0 program it was possible to identify which parameters control the conversion speed, the product purity, the energy expended, and the production rate